TI_GERICHTE 12.2018.38 vom 24. Mai 2018 , Incompetenza per territorio del giudice - spese e ripetibili - reclamo - TI Tribunale d'appello (2018)
Incompetenza per territorio del giudice - spese e ripetibili - reclamo